Efektivitas Warna dan Ketinggian Perangkap terhadap Nezara viridula L. pada Tanaman Kacang Panjang (Vigna sinensis L) - Sarah Malewan; Betty Sahetapy; Ria J Rumthe (JURNAL PERTANIAN KEPULAUAN, 2022)
An important pest that attacks long bean plants is the green ladybug (Nezara viridula L.). Green ladybug attacks cause the young pods to become empty and deflated, because the seeds do not form and the pods fall. Several field tests showed that yield loss by one adult N. Viridula per two plants caused pod damage by 49%. The aim of the study was to determine the color and height of the traps that were effective in trapping the green ladybug (Nezara viridula L.). The study was conducted in Taeno hamlet, Rumah Tiga Village, Teluk Ambon District from April to June 2022. The study used a Randomized Block Design (RAK) with 2 treatments. The first treatment was a trap color consisting of 3 levels, namely red, yellow and green. The second treatment was the height of the trap which consisted of 3 levels, namely the height of the trap 1 m, 1.5 m, and 2 m above ground level. The results obtained information that the interaction between the red trap color and the 1.5 m trap height had a significant effect on the number of green ladybug populations trapped in the 1st to 4th observations. -3 is found in the use of yellow traps, while in the 4th observation the interaction between green traps with a trap height of 1.5 m.